Gene variation impact on prostate cancer progression: Lymphocyte modulator, activation, and cell adhesion gene variant contribution. Issue 14 (29th June 2022) - Casadó‐Llombart, Sergi; Ajami, Tarek; Consuegra‐Fernández, Marta; Carreras, Esther; Aranda, Fernando; Armiger, Noelia; Alcaraz, Antonio; Mengual, Lourdes; Lozano, Francisco
Abstract: Background: The view of prostate cancer (PCa) progression as a result of the interaction of epithelial cancer cells with the host's immune system is supported by the presence of tumor infiltrating lymphocytes (TILs). TILs fate and interaction with the tumor microenvironment is mediated by accessory molecules such as CD5 and CD6, two signal‐transducing coreceptors involved in fine‐tuning of T cell responses. While the nature of the CD5 ligand is still controversial, CD6 binds CD166/ALCAM, a cell adhesion molecule involved in progression and dissemination of epithelial cancers, including PCa. The purpose of the present study was to determine the role of CD5, CD6, and CD166/ALCAM gene variants in PCa. Methods: Functionally relevant CD5 (rs2241002 and rs2229177), CD6 (rs17824933, rs11230563, and rs12360861) and CD166/ALCAM (rs6437585, rs579565, rs1044243, and rs35271455) single nucleotide polymorphisms (SNPs) were genotyped in germline DNA samples from 376 PCa patients. Their association with PCa prognostic factors, namely biochemical recurrence (BCR) and International Society of Urological Pathology (ISUP) grade was analyzed by generalized linear models and survival analyses. Result: Proportional hazards regression showed that the minor CD6 rs12360861 AA and CD166/ALCAM rs579565 AA genotypes were associated with earlier BCR, with hazard ratios of 2.65 (95% CI: 1.39–5.05, p  = 0.003) and 1.86, (95% CI: 1.02–3.39, p  = 0.043), respectively. Individually, none of the analyzed SNPs was significantly associated with ISUP grade, but haplotype analyses revealed association of the CD5 rs2241002 C ‐rs2229177 T haplotype with ISUP grade ≥2, with odds ratio of 1.52 (95% CI: 1.05–2.21, p  = 0.026). Conclusion: The results show the impact on PCa aggressiveness and recurrence brought about by gene variants involved in modulation of lymphocyte activation ( CD5, CD6 ) and immune‐epithelial cell adhesion ( CD166/ALCAM ) in PCa aggressiveness and recurrence, thus supporting a role for host immune response in PCa pathophysiology.